Rights and freedoms in the constitution of Madinah in the light of international human rights law - Elshobake, Mohammed R. M. (2023)
The Constitution of Madinah is the first constitutional law in Islam that was established by the Prophet Muhammad (peace and blessings be upon him) after the migration from Mecca to Madinah to regulate relations between Muslims from immigrants (al-Muhajireen) and supporters (al-Ansaar), as well as to regulate the relationship between Muslims and Jews residing in Madinah. It included a set of provisions, including those related to rights and freedoms. Through doctrinal and content analysis, this paper aims to clarify the rights and freedoms that the Prophet (peace and blessings be upon him) set in the Madinah constitution centuries before the emergence of international human rights law. This paper will give a brief overview of the constitution of Madinah, then discuss the political, civil, and judicial human rights contained therein, as well as explain the social and economic rights contained in the Madinah constitution. The findings of the paper prove the originality of Islamic thought and its precedence over man-made laws in determining humanitarian principles and human rights.